Velhice, ideologia e crítica: uma análise sobre a participação, protagonismo e empoderamento dos (as) velhos (as) nos espaços conferências - Costa, Joice Sousa [UNESP] (2015)
This work analyzes the social productions of stereotypes about aging process and AGING, in contemporary times, highlighting its influence in participation, leadership and empowerment of old people in conferences spaces of rights. for this purpose, it was necessary a critical understanding about the social productions of aging process and old age in the whole perspective,debating about the ideological placement in the production in quotidian and we argue the political function of lectures, mainly because we analyze the I Conferência Municipal dos Direitos da Pessoa Idosa at Franca- SP. we used the dialectical historical materialism method that enables the contradictory apprehensions of the movement of reality. the research is documental type, because it analyzes the internal regulation and final report of I Conferência Municipal dos Direitos da Pessoa Idosa at Franca- SP. . we used qualitative approach. for the analysis of data we use the method called content analysis. the results of this research indicate that there is an ideological political speech that consigns to the homogenization of old age and it tries to hide the social exclusion conditioned by the capitalism system and this same ideological passes by the concepts about participation, leadership and empowerment of old people, and they have been understood by the reduction and individualism perspective, a fact that impacts directly in aging movement that in lectures built a fruitful discussion about rights and services, however, this process that values to privatization of social struggles has been influencing the old age movement, trying to demoralize old people, although, in municipal lecture analysis we have identified the distance between the proposes and the theme of lecture that indicates strength of the aging